2021
DOI: 10.3389/fmicb.2021.716281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Fermentation Activities and Volatile Flavor Profiles of Chinese Rice Wine Fermented Using an Artificial Starter, a Traditional JIUYAO and a Commercial Starter

Abstract: In this study, an artificial starter culture was prepared using the core microbial species of JIUYAO to produce Chinese rice wine (CRW). The fermentation activity and flavor profiles of CRW samples fermented with traditional JIUYAO, a commercial starter culture, and our artificial starter culture were compared. The optimal protectant combination for lyophilization of the artificial starter was established as 15.09% skim milk, 4.45% polyethylene glycol, 1.96% sodium glutamate, and 11.81% maltodextrin. A compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…These results are in line with the results reported by Chen et al . (2021a, 2021b), who found that the acid content of Chinese rice wine was between 5.40 and 7.35 g L −1 . According to the Chinese standard rice wine (NYT1885‐2017) (The Ministry of Agriculture & Rural Affairs of China, 2017), the limitations of total sugar and acid contents are not below 25 and 0.5–10 g kg −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with the results reported by Chen et al . (2021a, 2021b), who found that the acid content of Chinese rice wine was between 5.40 and 7.35 g L −1 . According to the Chinese standard rice wine (NYT1885‐2017) (The Ministry of Agriculture & Rural Affairs of China, 2017), the limitations of total sugar and acid contents are not below 25 and 0.5–10 g kg −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Floral and honey are the odour features of β‐phenethyl acetate. Moreover, long‐ and middle‐chain fatty acid esters were deemed the main representative aroma in Huangjiu (Chinese rice wine) (Chen et al ., 2021a, 2021b). Middle‐chain fatty acid ethyl esters had an obvious impact on the aroma attributes of the fruity and full body in rice wine (Yang et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Total phenolics and flavonoids in food were confirmed to have antioxidant function (Chen, Hui, et al, 2021 ; Chen, Liu, et al, 2021 ). Chrysanthemum and glutinous rice in this study were also proved to contain these functional components, which were important indicators for evaluating the functionality of products (Cai et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Octanoic acid, phenoxyl alcohol, 2‐methyl‐1‐propanol, benzaldehyde, 3‐methyl‐1‐butanol, ethanol, lauric acid, and other flavor substances were detected in both RW and FRW during aging time. Among these, phenoxyl alcohol was a unique flavor substance in RW, which could bring rose aroma; 3‐methyl‐1‐butanol with the aroma and spicy taste of apple brandy; benzaldehyde with the special smell of bitter almonds (Chen, Hui, et al, 2021 ; Chen, Liu, et al, 2021 ; Yang et al, 2022 ). As for the flavor markers of RW, they existed in the whole aging stage in a typical style, without changing after storage.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic nose (e-nose) technology, which can digitize the empirical odor expression, has been widely used in food industry and introduced into the field of TCM to evaluate product quality rapidly and objectively. [19][20][21][22] Combined with gas chromatography (GC) and e-nose technology, 23,24 the Heracles NEO ultra-fast gas phase electronic nose (Heracles NEO e-nose) is an advanced olfactive tool that can be used to separate and identify the volatile compounds in TCMs. The chromatographic peaks obtained by GC are regarded as markers which can be used to obtain overall information about volatile constituents (also known as fingerprinting).…”
Section: Introductionmentioning
confidence: 99%